International Monetary Fund Annual Report 2018 : Building a Shared Future. (Annual Report of the Executive Board; Annual Report of the Executive Board, 2018)
The past year was one of growing economic anxiety tied to skepticism about both economic integration and an international approach to economic policy making. To help make globalization work for all, the IMF focused on providing policy advice in many macro-critical areas.